Environmental and physiological conditions that led to the rise of calcifying nannoplankton in the Late Triassic - Hohn, Sönke; Dal Corso, Jacopo; Hoke, Kim Lisa; Thoms, Silke; Merico, Agostino (Frontiers in Earth Science, 2023)
The rise of calcifying nannoplankton in the Late Triassic (237-201 Ma) had profound consequences for the carbonate buffering capacity of the ocean. Research on the appearance of calcification typically focuses on the reasons that made this process successful on a global scale. The underlying environmental and physiological conditions that led to its appearance, therefore, are still obscure. Here we show that the rise of intracellular calcification is intrinsically linked to cellular calcium metabolism and to the prevention of calcium accumulation in the cytoplasm. Using gene tree analysis, we present evidence that the physiological machinery for calcification was already present in non-calcifying ancestor cells. Additionally, by modelling the energy demands for calcium transport in calcifying and non-calcifying cells, we demonstrate that intracellular calcification does not require additional energy investments. Since all eukaryotic cells export calcium across the plasma membrane, our findings indicate that the onset of intracellular calcification in Earth's history only required the activation of calcium transport proteins during their passage to the plasma membrane. Hence, intracellular calcification could have occurred at any time in the geologic past because physiological preconditions were already present, but a combination of favourable environmental factors may have helped calcifying nannoplankton to spread at the beginning of the Mesozoic, a time of catastrophic climate changes and mass extinctions that reshuffled life on Earth.